The Effects of High-Intensity Aerobic Exercise on Cognitive Performance After Stroke: A Pilot Randomised Controlled Trial. (April 2019) - Pallesen, Hanne; Bjerk, Maria; Pedersen, Asger Roer; Nielsen, Jørgen Feldbæk; Evald, Lars
Background: Aerobic exercise is an effective treatment to improve aerobic capacity following stroke and might also improve cognitive impairments in sub-acute stroke survivors. The aim of the study was to assess the effect of high-intensity aerobic exercise on cognitive impairments in sub-acute stroke survivors. Methods: A pilot, randomised controlled trial on the effects of aerobic exercise on cognitive impairments of stroke patients in the sub-acute (1-3 months) phase was conducted. Thirty patients with moderate cognitive impairments (maximum score of 5 on at least two items on the cognitive subscales of the Functional Independence Measure [FIM]) were included in the study and randomly assigned to either the intervention group – performing high-intensity aerobic exercise (above 70% of maximum heart rate), or the control group – performing low-intensity aerobic exercise (below 60%). Patients in both groups exercised for 50 min twice a week for 4 weeks. Primary neuropsychological outcome: Trail Making Test B. Results: Thirty stroke patients completed the interventions. The results showed that the high-intensity group, compared with the low-intensity group, achieved significant improvements on Trail Making Test B, which assesses processing speed and divided attention ( P  = .04 after training and P  = .01 at follow-up). However, the significant improvements on Trail Making Test B might relate to a ceiling effect in the control group. Conclusions: This study does not provide evidence to support that aerobic exercise can improve cognition in stroke survivors, even though significant improvement was revealed on the primary outcome in sub-acute stroke survivors following high-intensity aerobic exercise compared with low-intensity general exercise.